China-India relations in the contemporary world dynamics of national interest and identity - Lu, Yang (Postdoctoral fellow) (Routledge advances in South Asian studies, 2017)
Positioned in a social constructivist framework that emphasizes mutual perceptions and socialization, the book draws analytical leverage from two core concepts - national identity and national interest - to form the basis of the research inquiry. The author argues that the dynamics of national identity and national interest play an important role in determining their relations and shows how and why in the current international structure, including a context of accelerated globalization, their national identities as rising power and emerging power coupled with national interest of economic development have defined and directed their international positions and foreign policy-making.